Finite element analysis for engine crankshaft torsional stiffness. (8th November 2019) - Fan, Rang-Lin; Zhang, Chu-Yuan; Yin, Fang; Feng, Cheng-Cheng; Ma, Zhen-Dong; Gong, Hua-Bing
Accurate crankshaft torsional stiffness is important to build the lumped parameter model (LPM) for crankshaft torsional vibration analysis. For the crankshaft system of a four-cylinder in-line gasoline engine, a procedure to build the finite element model (FEM) is presented. And the applicability of two ways to set the equivalent mass or equivalent moment of inertia for piston-rod in FEM is declared. When building a lumped parameter model, the concept of rigid-rotation of the crank pin central section around the central line of the crankshaft is proposed, and a method to obtain the torsional angle of the central section is declared. What is more, three post-processing methods are presented to obtain the torsional stiffness coefficients. According to three load cases of no-load, half load and full load, the tests are carried out. The simulation results of FEM and LPM, and the test results have good agreement with each other.